Experiences Influencing the Preparation of the Post-2027 EU Budget Framework - Ákos Kengyel (Intereconomics, 2025)
The article analyses the factors affecting the preparation of the post-2027 EU budget framework by examining the characteristics of the European Union's budget and the changes that took place between 2021 and 2027. The article draws lessons from the Multiannual Financial Framework and the NextGenerationEU programme and maps the factors influencing the planning of the post-2027 budget. The analysis pays special attention to the consequences arising from the new approaches applied in connection with the NGEU.
Keywords: E61; F36; 330